Metabolite profile of sibutramine in human urine: a liquid chromatography-electrospray ionization mass spectrometric study - Link, Marek; Hakala, Kati S; Wsól, Vladimír; Kostiainen, Risto; Ketola, Raimo A (Journal of mass spectrometry, 2006)
We present a detailed experimental approach to detection and subsequent structural characterization of unknown metabolites of sibutramine, using liquid chromatography-mass spectrometric techniques. The full-, precursor ion, and constant neutral loss scan modes of a triple quadrupole mass spectrometer were used for screening sibutramine metabolites in human urine. The structural assessment of unknown metabolites was based on MSn ion trap mass spectrometric analysis and comparison of MSn spectra between the standards and compounds detected. Two phase-I (M1 and M2) and eight phase-II (M3-M6) metabolites of sibutramine were found in human urine. Metabolites M1 and M2, which were found as minor metabolites, originated from N-demethylation of sibutramine. Carbamoyl glucuronides formed from metabolites M1, M2, and their hydroxylated analogs were the main metabolites of sibutramine and were characterized by tandem mass spectrometric analysis and by the chemical modification of their structure. We demonstrate the usefulness of the chemical derivatization approach for estimation of the site of glucuronidation and propose the formation of hydroxylated regioisomers of metabolites M4 and M6.
Keywords: glukuronidy; Chromatography, Liquid; Biotransformation; Hydroxylation; Solvents; hydroxylace; rozpouštědla; indikátory a reagencie; Adult; dospělí; referenční standardy; chromatografie kapalinová; biotransformace; lidé; ženské pohlaví; Humans; Spectrometry, Mass, Electrospray Ionization; ethanol; Ethanol; cyklobutany; Indicators and Reagents; Reference Standards; antidepresiva; hmotnostní spektrometrie s elektrosprejovou ionizací; Cyclobutanes; Female; Antidepressive Agents; Glucuronides